Sunnatullah dalam Perspektif Al-Quran Menurut Ahmad Mustafa Al-Maraghi dan Buya Hamka - Mhd Rafi Ikram; Syamsuwir Syamsuwir (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
The term sunnatullah is often understood as destiny, but basically sunnatullah is not just that. To understand the sunnatullah, the author displays how the views of the two commentators on the meaning of this sunnatullah. This study uses a comparative method, by comparing the opinions of Maraghi and Buya Hamka, will get the meaning of the sunnatullah. From the research, it is concluded that 5 things are a reference in understanding the meaning of sunnatullah, such as everything that happens in the universe is sunnatullah, Allah SWT's habits towards the infidels who deny the Prophet and Messenger, Allah SWT's decision to anyone who has just repented when he saw the punishment Allah SWT, something that can not be changed and replaced based on maslahat and wisdom, and the help of Allah SWT for believers who uphold the truth.